The crystal structure of 3-(2-hydroxyphenyl)-4-phenyl-6-(p-tolyl)-2H-pyran-2-one, C24H18O3 - Wang Mengdan; Wang Junling; Guo Yafei; Lu Weiwei; Luo Jie; Ma Jun-Ying (Zeitschrift für Kristallographie - New Crystal Structures)
C24H18O3, monoclinic, P21/c (no. 14), a = 9.0474(7) Å, b = 19.9648(12) Å, c = 10.7153(3) Å, β = 104.175(2)°, V = 1876.6(3) Å3, Z = 4, Rgt(F) = 0.0459, wRref(F2) = 0.1183, T = 296 K.